KETERKAITAN RENSTRA KEMENDIKNAS DENGAN RENSTRA DINAS DIKPORA PROVINSI DI. YOGYAKARTA DAN RENSTRA DINAS DIKPORA KABUPATEN SLEMAN - , Agus Sugiharto, S. Pd ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The study was aimed to identify and find out the linkages of strategic plans between education management institutions both in central and regional levels in similar ministry. It analyzed the linkages of inter strategic plans and factors that might influence the linkage. This research was necessarily conducted to determine the relationship of education development planning between the center government and regional office post of the implementation of regional autonomy which was accordingly meant the implementation of autonomy in education. In the autonomy government system, âSKPDâ (a working unit of regional government) prepares ârenstraâ (strategic planning documents) based on âRPJMâ (midium termed-development plan) and âRPJPâ (long termed-development plan). As âSKPDâ is hierarchically under the ministry, the strategic plans should accordingly be ministry-plan oriented. The results show that there is a positive linkage between strategic planning by the center level of educational institutions with those ones by the regional level. The linkages were identified through substantive and thematic approach. The similar and dominant aspects of each of the strategic plan were the core substances of the axis linkages of inter-strategic plan. The core substances are (1) improving the quality of âPTKâ (teacher and administrtive employee), (2) improving the quality and relevance of education, (3) expanding and distributing education services, (4) increasing educational facilities, (5) performing accountability and management of educational institutions. The factors influencing the strategic plan linkage which were based on 3 variables include (1) autonomy, (2) time of preparation, (3) and process of preparation. The results show that regional autonomy and time of preparation strongly influence the strategic planning linkages. While the formulation process of each strategic planning was not relatively effected.